NOTES ON MALAYSIAN MALVACEAE-I * - J. VAN BORSSUM WAALKES (Research Center for Biology, 1956)
Twelve new species of Hibiscus sect. Azanza DC. from the Malaysian region are described and illustrated. The genus Wilhelminia Hochr. is reduced to a synonym of this section, which requires the new combination Hisbiscus sciadiolepidns (Hochr.) Borss. for W. sciadiolepida Hochr. the only species of the genus.